ANALISIS KADAR LOGAM Fe DAN Mn PADA AIR MINUM DALAM KEMASAN (AMDK) DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Nisah, Khairun; Nadhifa, Husniah (AMINA, 2020)
This study aims to determine the levels of iron (Fe) and Manganese (Mn) in bottled drinking water (AMDK) using the Atomic Absorption Spectrophotometry (AAS) method. The bottled water used was 2 samples. In this study, obtained levels of Fe metals in the two AMDK samples using the instrument were Ë‚0,0002 while the calculation was -0.0468 mg/L. And the Mn metal content in both AMDK samples using the instrument was <0,0008 while the calculation was -0.0243 mg/L. The results of the analysis of Fe and Mn metals did not exceed quality standards stipulated by SNI 3553: 2015.